Histoenzymic Localization of Oxidoreductases in Pig Liver - Singh, Kirpal (Indian Journal of Veterinary Anatomy, 2020)
The present study was conducted on liver of six pigs collected from local slaughter house.The cryostat sections of 10 μm thickness of fresh unfixed tissues were cut at -23oC and incubated with different substrates for histoenzymic localization of different oxidoreductases. The study revealed a strong activity of succinic dehydrogenase, lactic dehydrogenase, malic dehydrogenase, glutamic dehydrogenase, alcoholic dehydrogenase, reduced nicotinamide adenine dinucleotide phosphate diaphorase, reduced nicotinamide adenine dinucleotide diaphorase and glucose-6-phosphatase dehydogenase in periportal hepatocytes as compared to centrilobular hepatocytes indicating that periportal hepatocytes may be more metabolically active as compared to centrilobular hepatocytes. The capsule, connective tissue, central vein, bile duct, hepatic artery and portal vein exhibited a weak activity of all enzymes.